FAMILIARISASI PRAKTIK UJIAN KOMPREHENSIF BAGI TARUNA PELAYARAN MENGHADAPI UJIAN KEAHLIAN PELAUT - Narto, Amad; Suganjar; Kundori, Kundori; Indah Suryani, Encis; Fauziningrum, Endah; Haryadi, Sugeng (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
The Seafarer's Skills Test (UKP) is a competency evaluation system that must be followed by sailors to obtain a skills certificate according to their level and field. The purpose of this activity is to provide an introduction and understanding to maritime cadets regarding the machinery system on board the ship so that cadets can prepare themselves for the comprehensive seafarer's skills exam practice. The method used in implementing this activity is to use a practical method, namely participants practice all the scenarios that have been explained previously to determine the extent of the cadets' knowledge and abilities in understanding the given practical scenarios and at the beginning a pre-test is given and at the end of the familiarization the participants are given a post-test questionnaire. The results of this activity are an increase in the understanding of cadets from 7 cadets or 35% to 16 cadets or 80% after participating in the familiarization activity. Meanwhile, cadets who do not understand have decreased significantly from 13 cadets or 65% to 4 cadets or 20%. This means that cadets are able to understand the structure and format of the exam that will be faced, recognize the types of scenarios and the time given so that cadets are prepared to face the comprehensive seafarer's skills exam. It is concluded that the simulator familiarization activity can increase the understanding of maritime cadets regarding the machinery system on board the ship so that cadets can prepare themselves for the comprehensive seafarer's skills exam practice.